(3eONd aj Yde GdfaS GdQjGVj s - (3YHO GdMcje QRb(B, (3YHO GdMcjes ((3GdGScfOQjI (B:s (3eDSSI YGde GdQjGVI ddfTQ(B,s, 2018)
(3JGQjN Yde GdfaS GdQjGVj h eagheg h CgOGag R eGgjI h aQhY h eLGdGJ Yde GdfaS GdQjGVj ceG Je JfGhd GdeQGMd h GdNUGFU GdfaSjI ddfeh h cPG GdTNUjI GdQjGVjI h OhGaY GdfTGW GdQjGVj h GfaYGdGJg h GdJhJQ GdfaSj aj GdeLGd GdQjGVj h GdJWQb Gdi GdYOhGf aj GdDjGVI h CNjQG GdEYOGO GdfaSj ddQjGVjjf (B.s
(3eQGLY U(B.279s
Keywords: (3GdJQHjI GdHOfjI (B- (3GdLhGfH GdfaSjIs